Spécificité des dimensions temporelle et contextuellde l'aide spécialisée à dominante pédagogique - Christine Pierrisnard; Marie-Paule Vannier (Nantes Université, 2012)
The question of the specificity of specialized educational help appears in a recurring way in specialized teacher education. This contribution discusses the relevance of two hypotheses: temporal and contextual. The contextual hypothesis makes echo for a conception of the human activity as an adaptive response of the subjects to the particular situations which they meet. In other words, the objective characteristics of the situation, in terms of change of place, of persons, of frame, would base the specialized practices. The professionals recognize as determining contextual element is to interacting with a small group of learners. The study of the temporal hypothesis shows that the specificity of a specialized help is not reduced "to take time" but should encourage construction of new temporal representations allowing the learner to think his learning.